Microscopic polyangiitis in an unassuming child with arthritis: A case report - Neha Da Rocha,; Prashant Prabhu,; Gordon Politano Martins,; Annely Dlima,; Maria Silveira, (Indian Journal of Case Reports, 2021)
Microscopic polyangiitis is a rare vasculitis in childhood that primarily affects the kidneys and lungs. Here, we present the case of a 9-year-old boy who presented with fever and arthritis of the left knee and ankle. Investigations incidentally revealed high creatinine and microscopic hematuria. Perinuclear anti-neutrophil cytoplasmic antibody (pANCA) and renal biopsy were suggestive of microscopic polyangiitis. The patient was given steroids and cyclophosphamide; however, he expired of a catastrophic diffuse alveolar hemorrhage. This case highlights the need to keep ANCA-associated vasculitis in mind during workup for hematuria and unexplained acute kidney injury to aid in early diagnosis and management of the underlying condition.